2013
DOI: 10.4049/jimmunol.1300279
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Role of C1q in Bacterial Infections: FacilitatingStreptococcus pneumoniaeAdherence and Invasion of Host Cells

Abstract: Streptococcus pneumoniae (pneumococcus) is a major human pathogen, which evolved numerous successful strategies to colonize the host. In this study, we report a novel mechanism of pneumococcal–host interaction, whereby pneumococci use a host complement protein C1q, primarily involved in the host-defense mechanism, for colonization and subsequent dissemination. Using cell-culture infection assays and confocal microscopy, we observed that pneumococcal surface-bound C1q significantly enhanced pneumococcal adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 55 publications
(61 reference statements)
6
23
0
Order By: Relevance
“…Taken together, the data suggest that C1q interacts primarily via its C-terminal globular heads with PepO. Indeed, this is in accordance with our recent finding, that C1q interacts directly in an antibodyindependent manner via its C-terminal globular heads with the pneumococcal surface-presented protein(s) and is functionally active (22). Apart from PepO, C1q will likely interact with other bacterial proteins as well as C-reactive protein and specific antibodies that both bind to the bacterial surface.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Taken together, the data suggest that C1q interacts primarily via its C-terminal globular heads with PepO. Indeed, this is in accordance with our recent finding, that C1q interacts directly in an antibodyindependent manner via its C-terminal globular heads with the pneumococcal surface-presented protein(s) and is functionally active (22). Apart from PepO, C1q will likely interact with other bacterial proteins as well as C-reactive protein and specific antibodies that both bind to the bacterial surface.…”
Section: Discussionsupporting
confidence: 92%
“…In turn, C1q functions as a molecular bridge between pneumococci and the host facilitating pneumococcal adherence and invasion (22). In the present study, we identified the multifunctional pneumococcal protein endopeptidase O (PepO) as the C1q ligand at the bacterial surface.…”
mentioning
confidence: 88%
See 3 more Smart Citations